Market Potential of Mobile Halal Poultry Slaughterhouses in Banten - Diqbal Satyanegara; Galih Ginanjar Saputra (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This research explores the connection between students’ learning styles and their vocabulary  achievement among second-grade learners. Utilizing a correlational research approach, the study  gathered data through a questionnaire addressing visual, auditory, and kinesthetic learning  preferences, along with a vocabulary achievement test. The participants included 25 students from  Class C. Data were analyzed using the Pearson Product-Moment correlation method. The results  show a strong positive relationship between each learning style and vocabulary achievement, with  correlation values of r = 0.838 for visual, r = 1.000 for auditory, and r = 0.923 for kinesthetic styles.  These findings suggest that students' preferred learning styles significantly impact their vocabulary  acquisition. The study emphasizes the need for teachers to acknowledge and adapt to various learning  styles in their teaching methods to support better vocabulary learning. It also recommends future  studies with broader and more varied participant groups to allow for generalization and deeper  exploration of causal links.